Upstream moisture sources and circulation patterns controls Asian monsoon hydroclimate over the past 20,000 years - Zhang, Jian; Liang, Ming-Qiang; Li, Jun-Yun; Wu, Yao; Xue, Yan-Xia; Sun, Wen-Jun; Liu, Xiang-Zhuo; Chen, Jin-Ke; Chen, Chao-Jun; Li, Ting-Yong (Quaternary science reviews, 2025)
Speleothem oxygen isotope records (δ18O) from caves in the Asian monsoon region have been widely utilized to reconstruct paleo-monsoon variability. However, interpreting these records remains challenging due to conflicting hypotheses about their relationship with Asian Summer Monsoon (ASM) strength and regional rainfall patterns. In this study, we analyzed 15 cave stalagmite δ18O records collected across East and South Asia, covering the last 20,000 years. Our analysis focuses on key climatic events, including Heinrich Stadial 1 (HS1), the Bølling-Allerød warm period (BA), and the Younger Dryas (YD), to explore the driving force of Asian summer monsoons from both high-latitude North Atlantic climate and lower-latitudes atmospheric circulation patterns. The results revealed that speleothem δ18O variations were predominantly influenced by shifts in upstream moisture sources, particularly from low-latitude regions in the Indian and Pacific Oceans, as evidenced by both observational data and model simulations. We demonstrated that δ18O records from Chinese caves reflect not only local rainfall dynamics but also broader influences from upstream moisture sources.
Online verfügbar 2 June 2025, Version des Artikels 2 June 2025
Gesehen am 27.10.2025